Abnormal Lipid Profile and its Association with the Type of Disease Modifying Antirheumatic drugs among Rheumatoid Arthritis Patients - Muhammad Tauseef Javed, Muhammad Maqsood, Masem Afzal, Fahad Aman Khan, Imran Khan, Umar Farooq Dar (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Patients suffering from rheumatoid arthritis (RA) may have abnormal lipid profile increasing the likelihood of cardiovascular diseases. Biological or targeted synthetic disease modifying antirheumatic drugs (DMARDs) have different mechanism of action than conventional DMARDs. Objective: To determine the effects of type of disease modifying antirheumatic drugs on prevalence of abnormal lipid profile among RA patients. Study design: Cross-sectional study Place and duration of study: Al-Aleem Medical College Lahore and Gujranwala Medical College Gujranwala from 1st December 2022 to 30th May 2023. Methodology: One hundred and sixteen rheumatoid arthritis patients were recruited from medical outpatient departments. Fasting lipid profile was assessed. Non obese patients of both genders, with diagnosis of rheumatoid arthritis were included. Smokers and obese patients were excluded. Results: 44.8% patients had abnormal lipid profile. 53% were on conventional DMARDs while 46% were using biological or targeted synthetic DMARDs. Abnormal lipid profile was associated with the duration of the disease greater than 5 years. It was not associated with type of DMARDs or severity of disease. Conclusion: The abnormal lipid profile is not associated with type of disease modifying antirheumatic drugs i.e. conventional or biological or targeted synthetic DMARDs. Keywords: Cardiovascular diseases, Conventional versus non-conventional DMARDs, Abnormal lipid profile, Arthritis.